2021
DOI: 10.1038/s41467-021-20994-y
|View full text |Cite
|
Sign up to set email alerts
|

New generation geostationary satellite observations support seasonality in greenness of the Amazon evergreen forests

Abstract: Assessing the seasonal patterns of the Amazon rainforests has been difficult because of the paucity of ground observations and persistent cloud cover over these forests obscuring optical remote sensing observations. Here, we use data from a new generation of geostationary satellites that carry the Advanced Baseline Imager (ABI) to study the Amazon canopy. ABI is similar to the widely used polar orbiting sensor, the Moderate Resolution Imaging Spectroradiometer (MODIS), but provides observations every 10–15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 67 publications
1
41
1
Order By: Relevance
“…However, since drylands feature heterogeneous vegetation, studies will need to investigate whether increases in temporal resolution with coarse spatial resolution are enough to offer an improvement in dryland phenology (Smith et al, 2019). Leveraging diurnal observations from GOES to estimate greenness trajectories and phenological transitions (Hashimoto et al, 2021;Wheeler and Dietze, 2021) across the Western Hemisphere, coupled with the ability to extract these transitions from AHI, SE-VIRI, and GOCI, can result in a near-global improvement in estimating seasonal vegetation growth and decline. The capacity of GOES to track events in plant phenology is shown in Figs.…”
Section: Plant Phenologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, since drylands feature heterogeneous vegetation, studies will need to investigate whether increases in temporal resolution with coarse spatial resolution are enough to offer an improvement in dryland phenology (Smith et al, 2019). Leveraging diurnal observations from GOES to estimate greenness trajectories and phenological transitions (Hashimoto et al, 2021;Wheeler and Dietze, 2021) across the Western Hemisphere, coupled with the ability to extract these transitions from AHI, SE-VIRI, and GOCI, can result in a near-global improvement in estimating seasonal vegetation growth and decline. The capacity of GOES to track events in plant phenology is shown in Figs.…”
Section: Plant Phenologymentioning
confidence: 99%
“…6.1. A recent review has also highlighted the use of geostationary imagers in monitoring landslides and flooding (Higuchi, 2021).…”
Section: Disturbance and Recoverymentioning
confidence: 99%
“…While the mechanism driving these variations in slope may not be immediately clear, it is important to note that there are open questions around the process of litterfall and its relation to precipitation and radiation in general. A recent study from Hashimoto et al (2021) demonstrated that the temporal density of optical data from the Advanced Baseline Imager (ABI) onboard the Diurnal variations (i.e. the difference between morning and evening overpasses) were generally small, particularly in the evergreen forests.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, incorporate observed data from vegetation dynamics and soil moisture is acutely necessary in order to evaluate uncertainties in vegetation indices such as NDVI and land-use changes. Incorporate the use of new generation geostationary satellites could help reduce these uncertainties and improve understanding of seasonality and vegetation dynamics in the tropical forests, which remains a challenge (Hashimoto et al, 2021).…”
Section: Hydrological Variables and Ndvi Relationshipmentioning
confidence: 99%